Prevalence of malnutrition in oncological patients (Research, Society and Development, 2020)
This study aims to analyze in the literature the prevalence of malnutrition in cancer patients. This is an integrative review. We used 12 articles available in the following databases: Scielo, Pubmed and Lilacs. The inclusion criteria for selection of these studies were: researches that approached the theme, published in English, Portuguese or Spanish in articles format comprising the period from 2012 to 2019, and that were indexed in the previously mentioned databases. As exclusion criteria: papers that did not present full abstracts in the databases and did not have a scientific character. According to the data obtained, it is observed that there is a high prevalence of malnutrition in cancer patients. The nutritional deficit caused by this condition directly implies the patient's immune system and response to treatment. In this way, it is necessary to include a professional nutritionist, since they are qualified and qualified to perform nutritional assessment and determine the best dietary management to achieve better response to treatment, as well as optimization and / or maintenance of nutritional status.